Environmental plasticity and stability of confectionery sunflower varieties in the conditions of the Eastern Forest Steppe of Ukraine - Chuiko, D.; Kryvoruchenko, R. (Scientific Progress & Innovations, 2023)
The adaptive potential of the plant is an important selection feature that contributes to the sustainable development of agriculture and obtaining stable harvests. High indicators of ecological plasticity and stability of sunflower allow obtaining stable and high-quality crops even in conditions of sudden changes in climate. The main goal of the research was to study the indicators of ecological plasticity and stability of sunflower genotypes for confectionery use Lakomka, Liuks, Myr, Donskyi Krupnoplidnyi and Shchelkunchyk. The task of the study was to evaluate the formation of the main structural elements of productivity of the studied genotypes in the conditions of the Left Bank Forest Steppe of Ukraine. The research was carried out according to the method of state variety testing, and the calculation of ecological plasticity and stability of varieties according to the method of Eberthart & Russel with the calculation of linear regression (bi) and the index of environmental conditions (Ij). It was established that the varieties Shchelkunchyk, Lakomka, Liuks and Myr had no significant differences on average during the study and were within the range of 180±22.7–185±27.1 cm, respectively, and the highest indicator was characterized by the variety Donskyi Krupnoplidnyi 230 ±40.8 cm. At the same time, a strong negative correlation (r=-0.86) was noted between plant height and seed oil content, the values of which averaged over the years in the range of 40.3±2.9–45.4 ±0.9 %. According to the results of field research in the period 2018–2021, high yield indicators of Lakomka, Liuks, Donskyi Krupnoplidnyi and Shchelkunchyk varieties were established in the range of 47.3–36.8 c/ha and the weight of 1000 seeds at the level of 108±27.0–99 ±22.8 g and positive correlation dependence between features r= 0.93, respectively. According to the calculations of ecological plasticity, it was established that the varieties Shchelkunchyk Lakomka and Donskyi Krupnoplidnyi (bi= 1.72; 1.41; 1.14) should be grown using intensive technologies, and the varieties Liuks and Myr (bi= 0.36) should be grown using extensive technologies. Among the studied sample of cultivar genotypes, the Lakomka variety with an index of σd²= 6.4 was noted for its environmental resistance.